Deadly Puppy Infection Caused by an MDR Escherichia coli O39 blaCTX–M–15, blaCMY–2, blaDHA–1, and aac(6)-Ib-cr – Positive in a Breeding Kennel in Central Italy - Mattioni Marchetti, Vittoria; Bitar, Ibrahim; Mercato, Alessandra; Nucleo, Elisabetta; Marchesini, Federica; Mancinelli, Marika; Prati, Paola; Scarsi, Giada Simona; Hrabak, Jaroslav; Pagani, Laura; Fabbi, Massimo; Migliavacca, Roberta (Frontiers in Microbiology, 2020)
Abstract Antimicrobial consumption in veterinary medicine has led to the spread of multi drug-resistance in clinically important bacteria, with the companion animals and their environment involved as emerging reservoirs. While CTX-M-15 and CMY-2 acquired β-lactamases have been widely detected in the bacterial population of companion and breeding animals in European area, DHA-1 enzymes have been rarely reported in veterinary medicine. The aim of the study was to characterize the Escherichia coli associated with mortality of a litter of Bulldog puppies in a breeding kennel located in Pesaro area, Central Italy. The E. coli strains O39 serotype were resistant to 3rd/4th generation cephalosporins, chloramphenicol, aminoglycosides, trimethoprim-sulfamethoxazole and ciprofloxacin, retaining susceptibility to carbapenems, colistin, fosfomycin and levofloxacin (by Microscan Autoscan4, EUCAST clinical breakpoints). Pulse Field Gel Electrophoreses (PFGE-XbaI) on five E. coli strains revealed the presence of a single profile. Whole Genome Sequencing (WGS) analysis revealed a complex resistome, harboring blaTEM-1b, blaCTX-M-15, blaOXA-1, aph(6)-Ib, aac(6’)Ib-cr, aac(3)-Ila, aph(6)-Id, aadA1, qnrB1, sul2, catA1, catB3, tetA and dfrA14 genes located on a 302597 bp IncHI2/HI2A plasmid. Moreover, blaDHA-1, qnrB4, mph(A), sul1 and dfrA17 determinants were carried on an 83429 bp IncFII plasmid. A blaCMY-2 determinant was carried on a 90249 bp IncI1 plasmid. Two IncX1 and IncX4 plasmids without antimicrobial resistance genes were also detected. The presence of lpfA, iss, astA and gad virulence factors was highlighted. This is the first report in Italy on an invasive infection in eight two-weeks old dogs caused by the same MDR E. coli O39 blaCTX-M-15, blaCMY-2, blaDHA-1 and aac(6′)-Ib-cr positive strain. The above MDR E. coli clone caused the death of the entire litter, despite amoxicillin-clavulanate and enrofloxacin administration. The tank for storage of the water used to prepare the milk-based meal for the litter was the suspected reservoir.